ATRT-15. TARGETING LIN28 REGULATED PATHWAYS IN NOVEL THERAPEUTICS DEVELOPMENT FOR CNS ATYPICAL TERATOID/RHABDOID TUMOR (CNS ATRT). (23rd April 2019) - Kannappan, Sunand; Gupta, Mehul; Zhang, Chunfen; Hofmann, Bradley; Chi, Susan; Hanson, Derek; Narendran, Aru
Abstract: INTRODUCTION: Elevated levels of LIN28A expression in AT/RT samples provide the rationale to search for agents that may interfere with cellular pathways regulated by this molecule. Ornithine decarboxylase (ODC) modulates eIF-5A through polyamines production and has been shown to directly influence the LIN28/Let-7 axis. The anti-protozoan drug α-difluoromethylornithine (DFMO) irreversibly inhibits ODC and its activity is potentiated by GC7 and Aurothioglucose (AuTG). METHODS: Bioinformatics: ATRT Pediatric Patient Dataset from Children's Brain Tumour Tissue Consortium was evaluated (n=32). In-vitro studies: Expression levels of LIN28 and ODC in three CNS ATRT cell lines, BT12, BT16 and KCCF1, were examined by western blotting. Cells were treated with increasing concentrations of DFMO, GC7 and AuTG and viability was measured by alamar blue assay. RESULTS: mRNA expression profile of patients suggest strong evidence of co-expression between three proteins: LIN28A – ODC1: 0.37 Pearson Coefficient (p = 0.037), ODC1 – EIF5A: 0.35 Pearson Coefficient (p = 0.049) and LIN28A – EIF5A: 0.54 Pearson Coefficient (p = 0.001). Drug sensitivity studies indicated DFMO, GC7 and AuTG were cytotoxic in-vitro . IC50 values of DFMO for BT12, BT16 and KCCF1 were 80uM, 50uM and 80uM respectively. GC-7 was cytotoxic at IC50 of 115uM, 25uM and 25uM and AuTG displayed IC50 of 15uM, 42 uM and 50uM. Markers of apoptosis, including PARP cleavage, were present at 48 hours although kinetics varied between cell lines. Drug combination studies showed significant synergy between DMFO and GC7. DISCUSSION: Data from this study identified alterations in expression and activity of components in LIN28 mediated pathways in ATRT. Interference in the LIN28 pathway by the tested drugs leads to apoptosis at physiologically attainable concentrations. Therapeutic efficacy can be further enhanced by mechanistically validated drug combinations. We discuss in detail the implications of these findings with respect to the biology and novel therapeutics development for ATRT.